Effect of Dietary Zinc Methionine Supplementation on Growth Performance, Immune Function and Intestinal Health of Cherry Valley Ducks Challenged With Avian Pathogenic Escherichia coli - Chang, Yaqi; Mei, Jia; Yang, Ting; Zhang, Zhenyu; Liu, Guangmang; Zhao, Hua; Chen, Xiaoling; Tian, Gang; Cai, Jingyi; Wu, Bing; Wu, Fali; Jia, Gang (Frontiers in Microbiology, 2022)
This study was carried out to evaluate the effects of supplemental zinc methionine (Zn–Met) on growth performance, immune function, and intestinal health of meat ducks challenged with avian pathogenic Escherichia coli (APEC). A total of 480 1-day-old Cherry Valley male ducks were randomly assigned to 8 treatments with 10 replicates, each replicate containing 10 ducks. A 4 × 2 factor design was used with four dietary zinc levels (0, 30, 60, 120 mg Zn/kg in the form Zn–Met was added to the corn–soybean basal diet) and challenged with or without APEC at 8-days-old ducks. The trial lasted for 14 days. The results showed that a dietary Zn–Met supplementation significantly increased body weight (BW) of 14 days and BW gain, and decreased mortality during 7–14-days-old ducks (p < 0.05). Furthermore, dietary 30, 60, 120 mg/kg Zn–Met supplementation noticeably increased the thymus index at 2 days post-infection (2 DPI) and 8 DPI (p < 0.05), and 120 mg/kg Zn–Met enhanced the serum IgA at 2 DPI and IgA, IgG, IgM, C3 at 8 DPI (p < 0.05). In addition, dietary 120 mg/kg Zn–Met supplementation dramatically increased villus height and villus height/crypt depth (V/C) of jejunum at 2 DPI and 8 DPI (p < 0.05). The TNF-α and IFN-γ mRNA expression were downregulated after supplemented with 120 mg/kg Zn–Met in jejunum at 8 DPI (p < 0.05). Moreover, dietary 120 mg/kg Zn–Met supplementation stimulated ZO-3, OCLN mRNA expression at 2 DPI and ZO-2 mRNA expression in jejunum at 8 DPI (p < 0.05), and improved the MUC2 concentration in jejunum at 2 DPI and 8 DPI (p < 0.05). At the same time, the cecal Bifidobacterium and Lactobacillus counts were increased (p < 0.05), and Escherichia coli counts were decreased (p < 0.05) after supplemented with Zn–Met. In conclusion, inclusion of 120 mg/kg Zn–Met minimizes the adverse effects of APEC challenge on meat ducks by improving growth performance and enhancing immune function and intestinal health.